Mechanically enhanced healable and recyclable silicone with dynamic hindered urea bond for flexible electronics. Issue 27 (21st June 2021) - Sun, Wenjie; Zhang, Lei; Wang, Shuang; Mao, Jiale; Luo, Jiaming; Chen, Yu; Cheng, Yonghong
Abstract : A silicone-containing dynamic hindered urea bond for flexible electronic substrates is developed with enhanced mechanical strength and healing ability simultaneously. Abstract : A silicone-containing dynamic hindered urea bond is demonstrated in this study for application in flexible electronics. Generated from isocyanate and piperazine, these dynamic hindered urea bonds endow silicone with high healing and recycling ability under mild conditions, together with an enhancement of more than 50% in tensile strength. By adjusting the piperazine and glycerol amount, the influences of the dynamic bond concentration and crosslinking density were also investigated. It was found that a higher piperazine amount improves the healing ability and recyclability, while increasing the glycerol fraction can enhance the tensile strength and elongation, but deteriorates the healing and recycling. Flexible conductive materials were prepared by filling the developed silicone with graphene. Admirable flexibility, healing ability and a sensitive response to resistance changes were prototyped by a flexible circuit with the light signal.